The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2147/ijn.s35832
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized carbon nanotubes: biomedical applications

Abstract: Carbon nanotubes (CNTs) are emerging as novel nanomaterials for various biomedical applications. CNTs can be used to deliver a variety of therapeutic agents, including biomolecules, to the target disease sites. In addition, their unparalleled optical and electrical properties make them excellent candidates for bioimaging and other biomedical applications. However, the high cytotoxicity of CNTs limits their use in humans and many biological systems. The biocompatibility and low cytotoxicity of CNTs are attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(69 citation statements)
references
References 155 publications
(215 reference statements)
0
65
0
Order By: Relevance
“…11 Among nanotechnology-derived materials, carbon nanotubes (CNTs) have stimulated a great interest for biomedical applications because of their unique mechanical, electrical, thermal, and spectroscopic properties. [12][13][14] It is important to note that recent studies showed that the functionalization of CNTs with different approaches increase the biocompatibility and decrease toxicity. [15][16][17][18] Among these studies, Guo et al studied the in vivo toxicity of functionalized multi-walled carbon nanotubes (f-MWCNTs) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…11 Among nanotechnology-derived materials, carbon nanotubes (CNTs) have stimulated a great interest for biomedical applications because of their unique mechanical, electrical, thermal, and spectroscopic properties. [12][13][14] It is important to note that recent studies showed that the functionalization of CNTs with different approaches increase the biocompatibility and decrease toxicity. [15][16][17][18] Among these studies, Guo et al studied the in vivo toxicity of functionalized multi-walled carbon nanotubes (f-MWCNTs) in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalization of the MWCNTs is of importance for providing dispersion of CNTs in an aqueous solution [7]. The MWCNTs used in the present study were produced using the chemical vapor deposition method, implying that these synthesized CNTs should have open ends and be highly susceptible to chemical reaction [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since their discovery CNTs have been used in many fields, such as in electrical and mechanical applications and for biological and medical purposes [6]. The lack of solubility in aqueous media has been a major technical barrier in biological and biomedical applications, but the recent development of methods to chemically modify and functionalize CNTs has made it possible to dissolve and disperse CNTs in water, making them more suitable materials for biological applications [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, drugs can adsorb through molecular interactions such as π–π stacking. [5760] These modifications can improve the solubility, biocompatibility for these hollow materials for biomedical applications.…”
Section: Nanocarriersmentioning
confidence: 99%